Kultura zaufania w organizacji. Istota – potrzeba – kształtowanie - Czajkowska, Maria (Annales. Etyka w Życiu Gospodarczym, 2008)
The article brings up the problem of making use of trust in organization management. Modern organizations and the conditions of their functioning enforce some inevitable changes in different areas of their activity. An attempt at adapting to these changes may be shaping trust culture and an opportunity to use this tool in organization management. The article contains elements of trust theory as well as organizational culture theory. It also presents an effort put into defining the guidelines for organization management concerning the trust culture shaping (on the basis of a theoretical model) and positive aspects of trust existing in an organization as well as a possibility of using it in management science as an effective tool.